The Role of Woman Business Owners in Implementing Transformational Leadership Style and Workforce Diversity through Job Satisfaction in Improving Employee Performance for Company Sustainability (West Science Business and Management, 2025)
The leadership role of women as business owners realizes gender equality and business sutainability. To ensure company sustainability, women as business owners are important in implementing a transformational leadership style and encouraging workforce diversity toward a more equitable and sustainable future in all business sectors. In this study, we examine transformational leadership style, and workforce diversity through job satisfaction in improving employee performance for health workers. Using a questionnaire survey method to capture 355 staff in the healthcare industry in Indonesia. The study’s findings indicate that long-term corporate sustainability is positively impacted by female business owners, transformational leadership, workforce diversity, job happiness, and employee performance. According to the findings of mediation effects, employee performance and transformational leadership style are partially mediated by work satisfaction. Employee performance and workforce diversity are not mediated by job satisfaction. This study offers implications for future empirically based research as well as theoretical and managerial insights.